Enhanced purification of plasmid DNA isoforms by exploiting ionic strength effects during ultrafiltration. Issue 4 (29th September 2015) - Li, Ying; Currie, David; Zydney, Andrew L.
ABSTRACT: The solution structure of plasmid DNA is known to be a strong function of solution conditions due to intramolecular electrostatic interactions between the charged phosphate groups along the DNA backbone. The objective of this work was to determine whether it was possible to enhance the use of ultrafiltration for separation of different plasmid isoforms by proper selection of the solution ionic strength and ion type. Experiments were performed with a 3.0 kbp plasmid using composite regenerated cellulose ultrafiltration membranes. The transmission of the linear isoform was nearly independent of solution ionic strength, but increased significantly with increasing filtrate flux due to the elongation of the highly flexible plasmid in the converging flow field into the membrane pores. In contrast, the transmission of the open‐circular and supercoiled plasmids both increased with increasing NaCl or MgCl2 concentration due to the change in plasmid size and conformational flexibility. The effect of ionic strength was greatest for the supercoiled plasmid, providing opportunities for enhanced purification of this therapeutically active isoform. This behavior was confirmed using experiments performed with binary mixtures of the different isoforms. These results clearly demonstrate the potential for enhancing the performance of membrane systems for plasmid DNA separations by proper selection of the ionic conditions. Biotechnol. Bioeng. 2016;113: 783–789. © 2015 Wiley Periodicals, Inc. Abstract : Effects of ionic strength on transmission of the different plasmid isoforms during ultrafiltration. The transmission of the supercoiled isoform increases significantly with increasing salt concentration due to a change in conformation associated with tighter supercoiling at high ionic strength. These effects were exploited to enhance the purification of the therapeutically active supercoiled isoform by ultrafiltration with proper selection of filtrate flux and ionic conditions.